Energy Utilization from Various Fat Sources by Broiler Chickens at Different Ages - Vieira , S.L.; Kindlein, L.; Stefanello, C.; Simoes, C.T.; Santiago, G.O.; Machado, L.P. (International Journal of Poultry Science, 2015)
Two studies were conducted to estimate nitrogen-corrected apparent metabolizable energy (AMEn) of different fat sources for broilers from 1 to 7 and 28 to 35 d of age. Corn-soybean meal diets with inclusions of 2, 4 and 8% degummed soybean oil (DSO), acidulated soybean soapstock (ASS), or pork lard (PL) (experiment 1) and coconut oil (CCO), palm oil (PO), or palm kernel oil (PKO) (experiment 2). Fats were added to the feeds at the expense of corn starch. Experiments were conducted in battery cages (0.72 m2) with 8 Ross × Ross 308 male broiler chicks each. Experimental diets were provided from 1 to 7 and 28 to 35 d and feed intake was recorded for each cage. Total excreta was collected from 3 to 7 and 33 to 35 d. Linear regressions at each age (Y = a + bx; Y = apparent available fat; x = level of fat added) allowed estimations of AMEn for each fat source as the product of the coefficient of apparent availability of fat (slope of the equations) multiplied by the gross energy of fat. Estimated values of AMEn (kcal/kg) from 1 to 7 vs. 28 to 35 d were, respectively, 8.348 vs. 9.283 (DSO); 7.706 vs. 8.533 (ASS); 8.219 vs. 8.781 (PL); 7.837 vs. 8.824 (CCO); 7.952 vs. 8.884 (PO) and 7.627 vs. 8.425 (PKO). Older chickens had average increases in fat AMEn of 8.3 and 10.5% compared to the younger ones. These responses present useful values for poultry feed formulation.